Flexible array beampattern synthesis using quadratic programming method - Tu, Lei (2015)
In some applications such as satellite communication, the transmission of signal is not restricted in a single direction, but within a wide range of azimuth angles. Obviously, the flat-top beampattern is preferred in this case, rather than the pointed-beam beampattern with a single peak. The objective of the thesis is to find a closed-form array synthesis method for flat-top beampattern with simple concepts and low computational load. With the Quadratic Programming applied, the focus of the research is to explore a proper mathematical function which describes the corresponding beampattern well. In the thesis, several new methods and its template functions are proposed for both pencil-beam and flat-top beampattern problems. Accordingly, the simulations and analysis of these proposed methods are presented.